Evaluating the Effectiveness for the Protection of the Environment Towards the Effects of Quarry Exploitation in Cameroon - Folefac, Tambo Ngosong (Studies in Social Science & Humanities, 2025)
In Cameroon in particular and the world at large, the exploitation and the processing of quarry resources by industries has brought about severe and adverse impacts on the environment and the local population within and around the quarry areas. This adverse impact ranges from environment degradation, pollution, health problems and environmental sustainability. To prevent this deplorable situation, the Cameroon Government has over the years instituted several mechanisms at the level of the ministries in charge of quarry exploitation and environmental protection in Cameroon as well institutions and industries involve in quarry exploitation. In order to attain our objective, qualitative research methodology has been adopted. This piece of work answers a specific research question which is how effective are the mechanisms for the protection of the environment from the effects of quarry exploitation in Cameroon and what are the challenges encountered? It is underpinned by the theory of environmentally responsible behavior. This theory advocates for responsible behavior from the communities as well as other stakeholders such as government, companies to adopt measures that minimize environmental impact. This includes implementing regulations, promoting community awareness about sustainable practices and encouraging the use of eco-friendly technologies. Finding reveals that although Cameroon has employed relevant mechanisms to address quarry activities and environmental protection, much is still required to be done. Based on the findings, the study strongly recommends the Cameroon Government to effectively implement its mining/quarry laws and make sure prior Environmental Impact Assessment (EIA), monitoring and evaluation are effective to make sure quarry industries operate within the legal frameworks while maintaining environmental sustainability.